KARAKTERISTIK KEUANGAN SEKOLAH DAN PENGAWASAN TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN SEKOLAH KEJURUAN DI BENGKULU UTARA - Minarti, Aznia; Fadli, Fadli; Puspita, Lisa Martiah Nila (JURNAL FAIRNESS, 2018)
This research aims is to determine the school financial characteristics and supervision on the effectiveness of financial management of Vocational School in North Bengkulu. In this study the object of research is the school treasurer, treasurer committee, Chairman of Komita, and principal. Characteristics of school finance at are good or run according to the rules. Monitoring of financial management is also indispensable in the financial management of vocational schools. The results of the study indicate that the respondents’ answers tend to agree to some point of activity carried out by the principal, school committee, treasurer, etc. The school financial management process should be efficient, cost-effective and financially appropriate, financial management must be well-directed and controlled in accordance with the original plan, program/activity, be open or transparent, and wherever possible using the capability/revenue outcome of funds which has been targeted through the previous plan is quite possible, so that the effectiveness of financial management can work well.